O Instituto Estadual de Educação do Pará - IEEP na memória de alunas e professoras (1940-1970) - Lobato, Vivian da Silva (2010)
This study proposes to answer the question: how is the daily life in Instituto de Educação do Estado do Pará IEEP re-lived based on the memory of its protagonists, teachers and pupils, from the period between the 1940 s and 1970 ? . The theretical-methodological reference is based upon the studies by Ecléa Bosi (1994; 2003) on memory and upon the theory on social memory by Maurice Halbwachs (1993). First of all documental research was carried out, so as to anchor IEEP s subjects , teachers and pupils narratives; then, data were collected on how the teachers remember and interpret IEEP in its various aspects, based on semi-structured interviews. In IEEP s archive and in the Belém Public Archive, record cards were found containing bureaucratic information on teachers and pupils, subject syllabi and some curricula for the course. The interviews were mostly one-to-one, some were conducted in pairs, with former pupils and teachers. The data was grouped according to categories of meaning and the content analyzed according to the theoreticalmethodological referential adopted for the research. Results show that IEEP was a space for education which aimed to strictly ensure content learning, but was also a cheerful coexistence space, where strong friendship bonds were established. The respondents narratives, spontaneously recreated the games, leisure and friends, more so than content. Responses regarding education and psychology in general are short. The curriculum provided deep theoretical education; while Law 4024/61 was in force, the curricular grid was more propaedeutical and encyclopaedic; under Law No. 5692/71, curricular education was slightly emptied as a consequence of the military regime, but still provided solid theoretical knowledge. Both assessment process and teaching attitudes are considered, respectively, traditional and strict by respondents, yet, it is important to stress that that was the paradigm at the time and the role prescribed for the teacher. However, the strictness of the curriculum, assessment and teachers demands are not perceived as absolutely negative by respondents, but rather as care for their learning. It is important to underline that the respondents show a loving longing for the educational mood at IEEP, given the school gave them quality education, which enabled them to enter the job market in good conditions, as well as providing them with information relating to practice, leisure, cultural insertion and friendships, in short, complete education, so publicized by the education theories in vogue today